Daily readings from Next level thinking : 10 powerful thoughts for a successful and abundant life - Osteen, Joel (USA FaithWords, 2018)
In Next Level Thinking, Joel Osteen wrote that we weren't created to go through life weighed down by addictions, dysfunction, guilt, or the past. God created us to be free. This companion devotional encourages readers to leave behind the negative mindsets, the scarcity mentality, and the limitations others have put on us, and shows us how to enjoy the positive life God meant for us with motivational daily readings and inspirational prayers.
Section I. Be a barrier breaker -- Section II. You are fully loaded -- Section III. The odds are for you -- Section IV. Move up to the next level -- Section V. Recognize your value -- Section VI. Live with the boldness of a son -- Section VII. Know you are loved -- Section VIII. Approve yourself -- Section IX. Get the contaminants out -- Section X. Remove the shame.
"90 devotions for a successful and abundant life"--Cover.
Keywords: Devotional literature; Thought and thinking -- Religious aspects; Attitude (Psychology) -- Religious aspects; Self-actualization (Psychology) -- Religious aspects; Christian life; Attitude (Psychology) -- Religious aspects; Christian life; Devotional literature; Self-actualization (Psychology) -- Religious aspects; Thought and thinking -- Religious aspects